Accounting System Software Based On Microsoft Access At Cv Semboyan Nafiri Indonesia - Winata Clevertan; Muhammad Taufik (Universitas Internasional Batam, 2023)
CV Semboyan Nafiri Indonesia is a Batam-based SMEs still utilize conventional bookkeeping processes. It resulted in inaccurate information being represented. Therefore the community service dedicated to this SMEs aims to build a database and bookkeeping system using Microsoft Access. Then, the system can be used to provide accurate representation of the business condition. Author conducted interviews and observation to map the needs and information about the business. The output generated from the bookkeeping system would be transactional forms, profit-loss statement, balance sheet, cash report and stock report. The output would guide the owner to keep track of inventory, monitor both expenses and revenue.